The Arab Spring between transformation and capture autonomous media and mobility in Tunisia - Pârvan, Oana, 1985- (New politics of autonomy., 2020)
"This book provides a detailed analysis of the narrative frame of the 'Arab Spring' and unpacks the process of the Tunisian revolution beyond national borders, discussing the importance of migration for different examples of collective action"--